Anorectal pathology amongst HIV infected patients attending the Douala General Hospital: a cross-sectional study. (March 2017) - Luma, Henry Namme; Eloumou, Servais Albert Fiacre Bagnaka; Fualefeh-Morfaw, Ellis Atemlefeh; Malongue, Agnes; Temfack, Elvis; Lekpa, Fernando Kemta; Donfack-Sontsa, Olivier; Ndip, Lucy; Ditah, Ivo Che
While gastrointestinal disease is common among HIV infected individuals, the prevalence and distribution of ano-rectal pathology has not been well studied in our setting. The objective of this study therefore was to determine the prevalence and determinants of ano-rectal pathology in HIV infected patients attending the Douala General Hospital HIV treatment centre. A hospital-based cross-sectional study was undertaken. We collected socio-demographic, clinical and laboratory data using a structured questionnaire and patients' files. Each study participant had a full physical and ano-rectal examination. We further studied factors associated with having at least one ano-rectal lesion by logistic regression reporting odds ratios (ORs) and their 95% confidence intervals (CI). We included 390 HIV infected patients. The mean age was 41 (SD: 8) years and 48% were men. Median duration since HIV diagnosis was 3 (interquartile range: 2–5) years and median CD4 cell count was 411 (interquartile range: 234–601) cells/mm 3 . Prevalence of ano-rectal pathology was 22.8% (95% CI: 18.7–27.3). Hemorrhoids and proctitis were most common lesions found; each in 10% of patients. From multivariate logistic regression, factors associated with ano-rectal pathology were CD4 < 350 cells/ml (OR: 2.1, 95% CI: 1.1–4.2), not on highly active antiretroviral therapy (OR: 2.2, 95% CI: 1.1–4.6), inpatient (OR: 2.3, 95% CI: 1.2–4.3), ano-rectal intercourse (OR: 5.0, 95% CI: 1.7–15.1), and more than one sexual partner (OR: 2.4, 95% CI: 1.3–4.2). Ano-rectal pathology is common amongst HIV infected patients. Care givers should actively investigate and treat them as this will improve the quality of life of people living with HIV/AIDS.